The effect of occupational exposure to organic dust on lung function parameters among African industrial workers: a systematic review and meta-analysis - Zemachu Ashuro; Berhanu Gidisa Debela; Chala Daba; Habtamu Endashaw Hareru; Samson Wakuma Abaya; Anthony L. Byrne (Frontiers in Public Health)
IntroductionInadequate ventilation and improper use of personal protective equipment are often observed in many occupational settings with a high risk of dust and other fine particle exposure. Workers who are exposed to dust at work may suffer from respiratory difficulties. Previous systematic reviews on organic dust exposure and its association with respiratory health outcomes did not provide a comprehensive assessment. Therefore, the objective of this systematic review and meta-analysis was to summarize the reported effects of organic dust exposure on lung function parameters among African industrial workers.MethodsA compressive literature search was conducted in PubMed, MEDLINE, Google Scholar, Embase, the Web of Science, African Journals Online, and ScienceDirect databases to identify relevant studies for the review. The Newcastle–Ottawa Scale (NOS) was used to assess the quality of the included studies. The lung function indices including forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), the FEV1/FVC ratio, and peak expiratory flow rate (PEFR) were obtained from primary studies and analyzed using STATA version 17. The I2 test was used to assess the heterogeneity of studies. We used a random-effects model to estimate the pooled standard mean difference in lung function indices between organic dust-exposed and non-exposed industrial workers. To analyze publication bias, funnel plots and Egger’s test were applied.ResultsIn this systematic review and meta-analysis, 32 studies involving 7,085 participants were included from 13,529 identified studies. The estimated mean differences with 95% confidence intervals were as follows: −0.53 [−0.83 to −0.36] L for FVC, −0.60 [−0.77 to −0.43] L for FEV1, −0.43 [−0.57, −0.29] L for FEV1/FVC, and −0.69 [−0.88 to −0.50] L/min for PEFR.ConclusionThis systematic review and meta-analysis revealed that the lung function indices, such as FVC, FEV1, FEV1/FVC, and PEFR, were statistically significantly lower among organic dust-exposed industrial workers compared to non-exposed industrial workers. Therefore, effective dust control measures should be implemented to protect workers from exposure to organic dust.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024527139.